Closing the loop: sericlo’s smart system for fashion sustainability - Hadi, Auberta Ardelia Putri; Hijjatul Putri, Aulia; Sri Defika, Anisa; Syahputra, Naufal Erva; Maisaroh, .; Muzakir, Mellisa Fitri Andriyani (2025)
SERICLO is a website that aims to address the textile waste problem caused by the fast fashion phenomenon. It offers various features, such as textile recycling, a preloved clothing marketplace, donation options, and AI-based redesign features integrated with AR. The website enables users to contribute to environmental conservation and support the implementation of a circular economy in the fashion industry. By combining artificial intelligence and forming partnerships with the recycling sector, SERICLO provides a comprehensive solution to reduce clothing waste and promote sustainable fashion consumption.